Trends in gastroesophageal reflux disease research: A bibliometric and visualized study - Zhang, Tai; Zhang, Beihua; Tian, Wende; Wei, Yuchen; Wang, Fengyun; Yin, Xiaolan; Wei, Xiuxiu; Liu, Jiali; Tang, Xudong (Frontiers in Medicine, 2022)
Background: Gastroesophageal reflux disease (GERD), a disorder resulting from the retrograde flow of gastric contents into the esophagus, affects an estimated 10% to 30% of the Western population, which is characterized by multifactorial pathogenesis. Over the past few decades, there have been many aspects of uncertainty regarding GERD leading to an ongoing interest in the field as reflected by a large number of publications, whose heterogeneity and variable quality may present a challenge for researchers to measure their scientific impact, identify scientific collaborations, and to grasp actively researched themes in the GERD field. Accordingly, we aim to evaluate the knowledge structure, evolution of research themes, and emerging topics of GERD research between 2012 and 2022 with the help of bibliometric approaches. Methods: The literature focusing on GERD from 2012 to 2022 was retrieved from the Science Citation Index Expanded of the Web of Science Core Collection. The overall publication performance, the most prolific countries or regions, authors, journals and resource-, knowledge- and intellectual-networking, as well as the co-citation analysis of references and keywords, were analyzed through Microsoft Office Excel 2019, CiteSpace, and VOSviewer. Results: A total of 8,964 publications were included in the study. The USA published the most papers (3,204, 35.74%). Mayo Clin ranked first in the number of articles published (201, 2.24%). EDOARDO SAVARINO was the most productive author (86, 0.96%). The most productive journal in this field was SURGICAL ENDOSCOPY AND OTHER INTERVENTIONAL TECHNIQUES (304, 3.39%). AMERICAN JOURNAL OF GASTROENTEROLOGY had the most co-citations (4,953, 3.30%). Keywords with the ongoing strong citation bursts were transoral incisionless fundoplication, eosinophilic esophagitis, baseline impedance, and functional heartburn. Conclusions: For the first time, we obtained deep insights into GERD research through bibliometric analysis. Findings in this study will be helpful for scholars seeking to understand essential information in this field and identify research frontiers.